Oropharyngeal Probiotic ENT-K12 as an Effective Dietary Intervention for Children With Recurrent Respiratory Tract Infections During Cold Season - Guo, Hongyan; Xiang, Xiaochen; Lin, Xuan; Wang, Qiang; Qin, Si; Lu, Xinyan; Xu, Jiawei; Fang, Ying; Liu, Yang; Cui, Jing; Li, Zhi (Frontiers in Nutrition, 2022)
Recurrent respiratory tract infections (RRTi) cause a high burden of disease and lead to negative impact on quality of life, frequent school/ work absenteeism and doctor visits, which remain a great challenge to pediatricians, because RRTi can increase the risk of various complications including antibiotic overuse and resistance which is one of the biggest threats to global health and there is no confirmed effective treatment. In the present study, we aimed to assess the clinical efficacy and safety of oropharyngeal probiotic ENT-K12 as a dietary intervention or a complementary treatment along with standard medical treatment during acute respiratory infections among children with recurrent respiratory tract infections during cold season. The results of this study show that comparing to practicing of standard medical treatment only, the complementary intake of oropharyngeal probiotic ENT-K12 can effectively reduce episodes of both acute and recurrent respiratory tract infections in school children, shorten the course of respiratory symptoms onset, reduce the use of antibiotics and antiviral drugs, and the absence days from both children’s school and parents’ work. Using oropharyngeal probiotics as a complementary dietary intervention to stabilize oropharyngeal microflora, specifically inhibiting respiratory pathogens and enhancing host immunity, could possibly be a promising approach to reduce RRTi burden and combating antibiotic resistance in long term, more clinical studies will be needed to further confirm the clinical practicing guide to ensure its clinical benefit.